2001
DOI: 10.1103/physrevlett.86.4223
|View full text |Cite
|
Sign up to set email alerts
|

Randall-Sundrum Model for Self-Tuning the Cosmological Constant

Abstract: The vanishing cosmological constant in the four-dimensional space-time is obtained in a 5D Randall-Sundrum model with a brane (B1) located at y = 0. The matter fields can be located at the brane. For settling any vacuum energy generated at the brane to zero, we need a three-index antisymmetric tensor field A(MNP) with a specific form for the Lagrangian. For the self-tuning mechanism, the bulk cosmological constant should be negative.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
142
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(145 citation statements)
references
References 20 publications
1
142
0
1
Order By: Relevance
“…Brane-world models of matter on the intersection of co-dimension 1 branes were studied and it was found that the Gauss-Bonnet term was needed in order to get a tension on the intersection in a natural way [13]. The Gauss-Bonnet term is the dimensionally continued 4-dimensional Euler density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brane-world models of matter on the intersection of co-dimension 1 branes were studied and it was found that the Gauss-Bonnet term was needed in order to get a tension on the intersection in a natural way [13]. The Gauss-Bonnet term is the dimensionally continued 4-dimensional Euler density.…”
Section: Introductionmentioning
confidence: 99%
“…The gravity of localised matter can be described by a boundary action. As in [13], we allow for the possibility of matter being localised on the surfaces of intersection also. The spacetime is divided up into polyhedral regions bounded by piece-wise smooth hypersurfaces-like a matrix of cells.…”
Section: Introductionmentioning
confidence: 99%
“…There were attempts of shielding the naked singularity of the self-tuning solutions with asymmetric warp factors by the blackhole-like horizon [6] but there is a no-go theorem associated with those too [7]. Instead of a canonical scalar field, an unorthodox action with a three form field or a dual scalar has been considered and shown to give rise to self-tuning solutions without naked singularity and with a finite 4d Planck mass [8][9][10][11][12]. (Later, unorthodox bulk matter has been considered in a different approach [13].…”
Section: Introductionmentioning
confidence: 99%
“…2 Self-tuning model with a three form field Self-tuning solutions with a three form field [8][9][10] and with a dual scalar [11,12,14] have been considered in the past. In this class of models the general action is [9] …”
Section: Introductionmentioning
confidence: 99%
“…They not only give a novel viewpoint of our world, but also open a new way to interpret many outstanding issues that the Standard Model (SM) can not interpret sufficiently, such as the hierarchy problem [1,2,[4][5][6][7], cosmological constant problem [8][9][10][11][12][13][14][15], the nature of dark matter and dark energy [16][17][18][19] and so on. Most of the early brane world models like the famous Randall-Sandrum (RS) branes were thin ones [1][2][3] neglecting the thicknesses of branes.…”
Section: Introductionmentioning
confidence: 99%